Chlorophyll fluorescence as a tool to select salinity-tolerant cowpea genotypes - Andrade, Jaima Ribeiro de; Maia Júnior, Sebastião de Oliveira; Barbosa, José Wilson da Silva; Alencar, Aryadne Ellen Vilar de; Jovino, Raphael Silva; Nascimento, Ronaldo do (Comunicata Scientiae, 2019)
The use of saline water reduces the growth and productivity of crops, so the need for techniques that make possible the use of this resource such as the use of salinity tolerant genotypes and efficient selection methods are of great importance. Thus, this study aimed to evaluate the tolerance of cowpea (Vigna unguiculata L. Walp.) genotypes to salt stress, through the chlorophyll fluorescence analysis. The experiment was conducted in a protected environment at the Federal University of Campina Grande, Paraíba, Brazil, using a completely randomized design in a 2 x 10 factorial arrangement, with three replications, consisting of two levels of irrigation water salinity (0.6 and 5.1 dS m-1) and ten cowpea genotypes: (G1: MNCO1-649F-2-1, G2: MNCO3-736F-2, G3: PINGO DE OURO-1-2, G4: BRS GURGUÉIA, G5: BRS MARATAOÃ, G6: MNCO2-676F-3, G7: MNCO2-683F-1, G8: MNCO3-737F-5-4, G9: MNCO3-737F-5-9, and G10: BRS TUMUCUMAQUE). The stem length, stem diameter, SPAD index, and chlorophyll fluorescence transients were evaluated. The G2 and G4 genotypes had the lowest reductions in the growth, stem diameter, initial fluorescence, and primary and maximum photochemical efficiency of PSII, proving to be tolerant to salinity. Chlorophyll fluorescence is a tool that can be used in the selection of salinity-tolerant cowpea genotypes.